2016
DOI: 10.3390/molecules21081091
|View full text |Cite
|
Sign up to set email alerts
|

Protein Tyrosine Phosphatase 1B Inhibitors from the Stems of Akebia quinata

Abstract: PTP1B deficiency in mouse mammary tumor virus (MMTV)-NeuNT transgenic mice inhibited the onset of MMTV-NeuNT-evoked breast cancer, while its overexpression was observed in breast cancer. Thus, PTP1B inhibitors are considered chemopreventative agents for breast cancer. As part of our program to find PTP1B inhibitors, one new diterpene glycoside (1) and 13 known compounds (2-14) were isolated from the methanol extract of the stems of Akebia quinata. All isolates were identified based on extensive spectroscopic d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
12
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(12 citation statements)
references
References 24 publications
0
12
0
Order By: Relevance
“…The structures of the new compounds ( 1 – 3 ) were elucidated on the basis of extensive NMR spectroscopic analysis, including a series of 2D-NMR experiments ( Figure 2 ) (HSQC, HMBC), and mass spectrometry data. The known compounds ( 4 – 10 ) were identified by comparison of their experimental spectral data with literature data [ 4 , 5 , 6 , 7 , 8 , 9 , 10 ].…”
Section: Resultsmentioning
confidence: 99%
“…The structures of the new compounds ( 1 – 3 ) were elucidated on the basis of extensive NMR spectroscopic analysis, including a series of 2D-NMR experiments ( Figure 2 ) (HSQC, HMBC), and mass spectrometry data. The known compounds ( 4 – 10 ) were identified by comparison of their experimental spectral data with literature data [ 4 , 5 , 6 , 7 , 8 , 9 , 10 ].…”
Section: Resultsmentioning
confidence: 99%
“…Its cytotoxicity was associated with the EtOAc-soluble fraction, which more potently inhibited PC-3 proliferation with 35.1 % (± 1.2) inhibition at the same concentration. The phytochemical investigation of the EtOAc-soluble fraction of the V. emarginatum MeOH extract yielded two new Δ 12 ursenetype triterpenoid coumaroyl esters (1 and 2), one new Δ 12 isopimarane-type diterpenoid glycoside (20), and two new irido-δ-lactone-type iridoids (21 and 22), together with 17 known pentacyclic triterpenoids (3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)) (▶ Fig. 1).…”
Section: Resultsmentioning
confidence: 99%
“…1). The known compounds were identified as 3β-O-(E)-feruloyl-19α-hydroxy-urs-12-ene-28-oic acid (3) [10], 3β-O-(Z)-feruloyl-19α-hydroxy-urs-12-ene-28-oic acid (4) [10], 3β-O-(E)-feruloyl oleanolic acid (5) [11], 3β-O-(E)-feruloyl ursolic acid (6) [11], ursolic acid (7) [12], pomolic acid (8) [13], rotundic acid (9) [13], 2α,3α,23-trihydroxyurs-12-en-28-oic acid (10) [14], euscaphic acid (11) [15], myrianthic acid (12) [15], rotundanonic (13) [16], 3-oxo-19,23,24-trihydroxyurs-12-en-28-oic acid (14) [17], maslinic acid (15) [18], arjunolic acid (16) [19], 2α,3α,23-trihydroxyolean-12-en-28-oic acid (17) [20], friedelin (18) [21], and epi-friedelinol (19) [21] based on their spectroscopic data, which were identical to literature values. The structures of compounds 1, 2, and 20-22 were elucidated by detailed analysis of standard spectroscopic data, including high-resolution electrospray ionization mass spectrometry (HRESIMS), IR spectroscopy, and 1D and 2D NMR and by comparison with the spectroscopic data of known analogs.…”
Section: Resultsmentioning
confidence: 99%
“…Because PTP1B and SHP2 are associated with multiple cancer-related diseases, as well as SHP2 is a potential immunomodulator, which alters autoimmunity and related immunopathology, controlling PTP1B and SHP2 activities is of significant therapeutic interest 30,31. Studies have indicated that some natural diterpenes reveal significant inhibitory effects on the PTP1B enzyme and are considered an anti-breast cancer agents 32…”
Section: Discussionmentioning
confidence: 99%